Atnoa1 mutation may induce temperature acclimation mechanisms in Arabidopsis thaliana - Majláth, Imre (Acta Biologica Szegediensis, 2011)
The present work was focused on evaluating the effect of the Atnoa1 mutation on temperature adaptation processes and on changes in the content of stress-related compounds, polyamines and salicylic acid. Freezing tests indicated that cold acclimation substantially increased the freezing tolerance of Atnoa1 mutant plants, similarly to the wild type, suggesting that the negative changes caused by the mutation in ATNOA1 do not substantially affect hardening processes. Atnoa1 mutation does not affect significantly the antioxidant enzymes Under control conditions in Arabidopsis plants; however, the cold induced increase in the activity of glutathione reductase was more pronounced in Atnoa1 than in the wild-type. Results suggest that Atnoa1 mutant Arabidopsis plants try to compensate for the negative effects of this mutation. These adaptation processes include the stimulation of photoprotection and alterations in the salicylic acid and polyamine compositions.